PELATIHAN PEMBUATAN PUBLIKASI ILMIAH GURU-GURU SMA N 2 TAMBANG KABUPATEN KAMPAR - Jufrizal Syahri; Rahmiwati Hilma; Hasmalina Nasution; Prasetya Prasetya; Rahmadini Syafri; Sri Hilma Siregar; Nurlaili Nurlaili (LPPM UMRI, 2018)
The writing of scientific writing is one of the efforts to develop the profession of teachers of SMA N 2 Tambang in Kampar regency. This training aims to equip teachers in terms of strategies to develop scientific papers properly in accordance with the guidelines of writing, and equip teachers in the publication procedures of scientific papers in the journal. The training of scientific writing is done by varied lecture method and practice. The lecture method is needed to explain the procedure for the preparation of scientific papers, including how to arrange classroom action research into a scientific paper. Methods of practice are needed to allow the participants to write scientific papers in the form of articles for journals. The training activities of the writing of scientific papers as a whole can be said to be well seen from the achievement of the target of the trainee, the achievement of the training objectives, the achievement of the planned material targets, and the ability of the participants in the mastery of the material. The supporting factors for the implementation of Community Service activities are the availability of experts in SMA N 2 Tambang, the enthusiasm of the participants, the support of the principal of the place of administration, and the supporting funds of the faculty.